تكوين الداعية بين الفقه والدعوة دراسة تحليلية لكتاب ثقافة الداعية يوسف القرضاوي - بالساسي, أمال; طلاب, عائشة; رحماني, خولة; زيد, فاطة; توانسة, ايمان (جامعة الوادي university of eloued, 2020)
يتناول بحثنا هذا دراسة جديدة هامة دراسة غائبة عند أغلب المسلمين في العالم الإسلامي, دراسة تحتاج إليها الأمة في الوقت الراهن ألا وهي تكوين الداعية بين الفقه والدعوة, وقد تطرقنا في بحثنا لدراسة تحليلية لكتاب الشيخ الدكتور يوسف القرضاوي ثقافة الداعية . كان هو السباق الذي تطرق لهذا الموضوع ونحن بدورنا ارتأينا أن نق وم بدراسة تحليلة لهذا الكتاب لأنه يعد منهجا علميا يجب الداعية هضمه, فهو أحد الكتب التي ترسخ لتكوين ثقافة إنسانية لمعرفة الثقافة اللازمة للداعية أن أردنا أن ننشئ مدرسة للدعاة أو كلية للدعوة أو أراد أحدنا أن يكون من نفسه داعية قادرا على التوجيه والتأثير, ولقد تبين لنا أن الداعية في حاجة إلى مجموعة من الثقافات ونذكر منها :الثقافة الدينية والثقافة التاريخية والثقافة العلمية الواقعية . Abstract Through this research, we deal with a new, important and absent study of most Muslims in the world. A study that the Islamic ummah needs at the present time, namely, the formation of the preacher between fiqh and da'wah. Through our research, we touch upon an analytical study of Sheikh Dr. Yusuf al-Qaradawi's book “The Culture of the Preacher,” and al-Qaradawi was the first to address this topic. Therefore, this book is considered a scientific approach that the Islamic preacher must master and understand in order to form and establish a human culture. And to know the necessary culture for the Islamic preacher, and if we want to establish a school for preachers, or if one of us wants to become a preacher someday capable of directing and influencing, he must be familiar with a group or a mixture of cultures, including religious culture, historical culture, and realistic scientific culture.
دعوة